Pediatric Autoimmune Encephalitis: Case Series From Two Chinese Tertiary Pediatric Neurology Centers - Zhang, Jianzhao; Ji, Taoyun; Chen, Qian; Jiang, Yanan; Cheng, Huan; Zheng, Ping; Ma, Wenqiang; Lei, Ting; Zhang, Yao; Jin, Yiwen; Wei, Cuijie; Wu, Ye; et al. (Frontiers in Neurology, 2019)
Background and purpose: We retrospectively analyzed the clinical characteristics of children with autoimmune encephalitis (AE) in two Chinese tertiary pediatric neurology centers. We also compared the anti-NMDAR encephalitis with and without co-positive MOG antibody, as well as the specific autoantibody positive AE and autoantibody-negative but probable AE. Methods: A retrospective study of children (0–18 years old) with AE in Peking University First Hospital and Children's Hospital Affiliated to Capital Institute of Pediatrics was carried out from May 2012 to January 2017. Demographics, clinical features, laboratory and imaging findings, outcome, and co-positive with MOG antibody were analyzed. Results: A total of 103 children had AE, 89 (86.4%) had anti-NMDAR encephalitis, 2 (1.9%) had anti-LGI1 encephalitis, 1 (0.9%) had anti-CASPR2 encephalitis, and 11 (10.7%) were diagnosed as autoantibody-negative but probable AE. Among the 89 children with anti-NMDAR encephalitis, 35 were males, and 54 were females. The follow-up time was 1–3 years. A total of 15 cases (15/89, 16.9%) with anti-NMDAR encephalitis had co-positive MOG antibody (serum or cerebrospinal fluid or both). These patients were more likely to experience relapse later in life (P=0.014). We had two cases with anti-LGI1 encephalitis, that is, one with sleep disorder onset, and the other one with seizure onset, both of which recovered after treatment. One case with anti-CASPR2 encephalitis was treated with antiepileptic drug and fully recovered. There were 11 cases diagnosed as autoantibody negative but probable AE who had relatively poorer outcome than those with autoantibody-positive AE (15.2%, 14/89). However, the difference was not significant (P=0.08). Only one 12-year-old girl with NMDAR-antibody AE had ovarian teratoma. Conclusion: Most subjects with AE in our Chinese cohort had anti-NMDAR AE, which had relatively good prognosis. Children with anti-LGI1 or anti-CASPR2 encephalitis were rare and showed good response on immunotherapy. Co-positive MOG antibody were relatively common in anti-NMDAR encephalitis, which was related to high relapse rate. In our study, the prognosis of autoantibody negative but probable AE seemed worse than that of specific autoantibody positive AE. Keywords: NMDAR, autoimmune encephalitis, child, prognosis